Determinants of Anemia among Children Aged 6–59 Months in Ethiopia: Further Analysis of the 2016 Ethiopian Demographic Health Survey - Melash Belachew Asresie; Gedefaw Abeje Fekadu; Gizachew Worku Dagnew (Advances in Public Health)
Background. Anemia among children is a global public health problem. The burden is high in developing countries including Ethiopia. Although there are some studies about anemia among children, there is a dearth of information about factors associated with anemia in Ethiopia. Therefore, this analysis was performed to identify factors associated with anemia among children aged 6–59 months in Ethiopia. Methods. We used the 2016 Ethiopian Demography and Health Survey (EDHS) data. EDHS was a community-based, cross-sectional study conducted from January 18, 2016 to June 27, 2016. The 2016 EDHS selected the participants using a two-stage stratified cluster sampling technique. A total of 8,462 children aged 6–59 months were included for this analysis. Both descriptive and logistic regression analyses were performed using Stata version14. A P value less than 0.05 at 95% confidence interval was set to test the statistical significance. Results. The analysis indicated that about 58% (95% CI: 55.1, 60.1) of children aged 6–59 months were anemic. Of those, 29.4% and 3.1% had moderate and severe anemia, respectively. The analysis revealed that stunted (AOR = 0.135, 95% CI: 1.13, 1.62) and underweight (AOR = 1.27, 95% CI: 1.04, 1.55) children had higher odds of being anemic. Besides, children aged 6–23 months (AOR = 1.39, 95% CI: 1.06, 1.82), 24–42 months of age (AOR = 1.26, 95% CI: 1.05, 1.51), and those with fever (AOR = 1.34, 95% CI: 1.07, 1.67) had higher odds of being anemic. Similarly, children from anemic mothers (AOR = 1.86, 95% CI: 1.58, 2.18) and poor households (AOR = 1.35, 95% CI: 1.09, 1.67) were at a higher risk of anemia. Children from households with large family sizes (AOR = 1.29, 95% CI: 1.03, 1.60), young mothers (15–24 years of age (AOR = 1.39, 95% CI: 1.06, 1.82) and 25–34 years of age (AOR = 1.26, 95% CI: 1.05, 1.51)), and developing regions (AOR = 1.44, 95% CI: 1.03, 2.02) also had higher odds of developing anemia. Conclusion. The overall prevalence of anemia among children aged 6–59 months in Ethiopia was high. Malnourished children (stunting and underweight); children with fever; children from anemic, uneducated, and young mothers; and children from large and poor families had higher odds to develop anemia. Therefore, preventing childhood illnesses and maternal anemia should be strengthened to reduce anemia among children.